Constitutional embodiment of the right of political asylum under the Iraqi Constitution in force 2005 - Ateiah Alkhagani, Gani Zkaier (Opción, 2019)
The issue of political asylum is of great and varying importance, especially in re- cent times. The motives that have given rise to this importance are increasing in size, aggravation and spread throughout the world, as evidenced by recent political and security instability in many countries of the modern world. A person may acquire political views contrary to the political system in his country, which is a sufficient ground for absconding and seeking recourse to other states for protec- tion, prevention of persecution and abuse of the world at large. This right must have been secured by any means, violation of rights and torture in his country which holds its nationality, especially in countries with totalitarian regimes. As security and safety are among the most basic rights that human beings need in the face of creation and the most basic rights which must be among the most important of these means is the constitution of the right of political asylum, in the sense that this right is enshrined in the constitutions of different countries on the basis that the Constitution is the supreme document and the highest law in each country all laws and internal laws issued therein shall be complied.